Staking claim : settler colonialism and racialization in Hawai'i - Rohrer, Judy (Critical issues in indigenous studies., 2016)
"Staking Claim analyzes Hawai'i at the crossroads of competing claims for identity, belonging, and political status. Judy Rohrer argues that the dual settler colonial processes of racializing native Hawaiians (erasing their Indigeneity), and indigenizing non-Hawaiians, enable the staking of non-Hawaiian claims to Hawai'i"--Provided by publisher.